A COPULA REGRESSION FOR MODELING MULTIVARIATE LOSS TRIANGLES AND QUANTIFYING RESERVING VARIABILITY. Issue 1 (8th October 2013) - Shi, Peng
Abstract This article proposes a claims reserving model for dependent lines of business with the accommodation of association among triangles by a copula function. We show that the family of elliptical copulas is a pretty convenient choice to capture the dependencies introduced by various sources, including the common calendar year effects. To quantify the associated reserving variability, we resort to parametric bootstrapping techniques for simulating the predictive distribution of outstanding liabilities and for calculating the three components of predictive uncertainty: the model error, the process error and the estimation error. Numerical analysis is performed for a portfolio of casualty insurance from a major U.S. insurer.